ANALISIS EFISIENSI PRODUKSI USAHATANI PADI LADANG DI KECAMATAN SIDOMULYO KABUPATEN LAMPUNG SELATAN - Suci Rodian Noer; Wan Abbas Zakaria; Ktut Murniati (Lampung University, 2018)
The research aims to know the income level and production’s efficiency of upland rice farming in Sidomulyo Subdistrict of South Lampung Regency. The Location of this research was chosen purposively with consideration that the area is upland rice production centers in Lampung. This research used a survey method and the data were collected in Nov-Dec 2016. The samples consist of 54 upland rice farmers selected using stratified random sampling method. The income level of upland rice farming is analyzed by using income analysis method. The production efficiency of upland rice farming is analyzed by using production stochastic frontier function analysis method. The results showed that the income level of upland rice farming in rainy season (November 2016 until March 2017) was provitable about Rp 1.381.414/ha, R/C value of total cost was about 1.22. The production efficiency level of upland rice farming was 89 percent (not efficienct yet).Key words : efficiency, income, production, upland rice